2019
DOI: 10.1021/acsenergylett.8b02346
|View full text |Cite
|
Sign up to set email alerts
|

Origin of Low Carrier Mobilities in Halide Perovskites

Abstract: Halide perovskites constitute a new class of semiconductors that hold promise for low-cost solar cells and optoelectronics. One key property of these materials is the electron mobility, which determines the average electron speed due to a driving electric eld. Here we elucidate the atomic-scale mechanisms and theoretical limits of carrier mobilities in halide perovskites by performing a comparative analysis of the archetypal compound CH 3 NH 3 PbI 3 , its inorganic counterpart CsPbI 3 , and a classic semicondu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

24
194
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 169 publications
(220 citation statements)
references
References 70 publications
24
194
0
2
Order By: Relevance
“…This phonon scattering is believed to be the key fundamental factor in establishing the intrinsic limit of the charge carriers mobility. More specifically, it has been recently suggested that this limit is set by the lower energy LO modes (3-20 meV) [58]. Therefore, the observed presence of such modes, common in all four compounds, seems to be the reason for the relatively low mobilities compared to classical inorganic semiconductors like Si and GaAs.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…This phonon scattering is believed to be the key fundamental factor in establishing the intrinsic limit of the charge carriers mobility. More specifically, it has been recently suggested that this limit is set by the lower energy LO modes (3-20 meV) [58]. Therefore, the observed presence of such modes, common in all four compounds, seems to be the reason for the relatively low mobilities compared to classical inorganic semiconductors like Si and GaAs.…”
Section: Discussionmentioning
confidence: 91%
“…By crossreferencing our results with the above mentioned previous works and other literature on the subject, we can assign the identified features of the low temperature spectra to the respective vibrational modes. In recent lattice dynamics calculations, Ponce et al [58] predict five modes for MAPI at 3, 4.3, 10.2, 14.4 and 21 meV. Asite displacement (i.e.…”
Section: Optical Phonons In the Orthorhombic Phasementioning
confidence: 99%
“…[41,42] Small and comparable effective masses of the electrons and holes can be predicted from the electronic band dispersion around the band edges,w hich contribute to the carrier mobilities. [43] However these mobilities,i nt he Pb-based HaPs in general, are considerably smaller than expected from the values of effective mass,a nd it has been suggested that this is due to phonon scattering by the relatively soft HaP lattice. [44] As the crystal cubic phase is transformed to the low-symmetry orthorhombic phase,t he metal-halide-metal bond angle decreases.A long with the increase in the E g ,t his decrease in bond angle increases both the effective carrier masses and Reproducedw ith permission.…”
Section: Electronic Structurementioning
confidence: 90%
“…As discussed in Ref. 66, the accuracy of the effective masses is improved by using a self-consistent, kdependent scissor shift. This approximation, which we call G 0 W 0 -∆ k , yields a wider bandgap of 3.85 eV.…”
Section: Gw Quasiparticle Correctionsmentioning
confidence: 99%